A Century of Cleansing Winchester. (2nd January 2016) - Gregory, Martin
Abstract : The provision of mains sewerage and the centralised collection of refuse are two of the most long-lasting infrastructure projects brought in by Victorian engineers. The Sanitary Act of 1866 required local Councils to supply 'a sufficient sewerage system and a supply of wholesome water', triggering a large number of schemes throughout the country. The City of Winchester is taken as an example of a city slow to implement the Act. When mains drainage came to the city, it was allied to a refuse destructor to supply energy to the pumping plant. Over a century of increasing population requiring sewerage and refuse services over an increasing area, the subsequent history of the plant provides an insight into the development of such services in a typical, medium-sized British town.